Phonological memory and sentence processing in South African L2 English-speaking children - Madziwo, Alexia Ruvarashe (University of the Witwatersrand, Johannesburg, 2023)
Out of the many factors that have impacted the state of education in South Africa (resulting in low literacy rates and high rates of academic failure), it is critical to investigate the linguistic implications on education. Comprehension has been pinpointed as a site of further research and intervention; therefore, this current study aimed to investigate the possible contributions that phonological short-term memory (pSTM) has on spoken sentence comprehension of South African second language (L2) English-speaking children from southern African Bantu language backgrounds. Discourse has claimed pSTM – a temporary auditory information memory store – to be an independent language process system from that of comprehension. However, it presents an interesting focal point for a few reasons including the following: i) L2 English-speaking children from southern African Bantu languages are confronted with the phonologically distinct English language in educational spaces; ii) children need to store sentences to process and respond to them; and iii) children’s complex linguistic skills have not yet been developed – thus, there is dependence on lower-level linguistic skills. In this study, 25 children from Polokwane, Capricorn District, participated in tasks to identify the effects of pSTM in relation to sentence processing. The researcher then analysed the developmental aspects of these processes. The corpus fell into two separate groups: i) the Grade 1, 6–7-year- olds and ii) the Grade 4, 9–10-year-olds. Three tasks were presented to the participants: i) the nonword repetition task to assess their pSTM capacity, ii) a sentence-repetition task, and iii) a sentence-picture naming task. The results indicated that pSTM capacity was present from age 6 and improved with age. However, there was no clear contribution to sentence processing; despite high pSTM capacity results, sentence comprehension and repetition results remained low. In this study, we also found the following: i) syntax was a marker for comprehension issues; ii) sentence repetition showed better results than comprehension, indicating a possibly stronger link between pSTM and sentence repetition; iii) possible language interactions during pSTM disyllabic recall were noted.
A research report Submitted in fulfillment of the requirements for a Master of Arts Research Dissertation in Linguistics, In the Faculty of Humanities , School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2023
Keywords: phonological short-term memory (pSTM); sentence processing; sentence comprehension; oral sentences; bilingualism; language development; nonword repetition (NWR); sentence repetition; sentence-picture naming; UCTD; SDG-4: Quality education